Multi objective multi refinery optimization with environmental and catastrophic failure effects objectives - Khogeer, Ahmed Sirag, author; Karim, M. N., advisor (Colorado State University. Libraries, 2005)
Petroleum refining is a capital-intensive business. With stringent environmental regulations on the processing industry and declining refining margins, political instability, increased risk of war and terrorist attacks in which refineries and fuel transportation grids may be targeted, higher pressures are exerted on refiners to optimize performance and find the best combination of feed and processes to produce salable products that meet stricter product specifications, while at the same time meeting refinery supply commitments and of course making profit. This is done through multi objective optimization. For corporate refining companies and at the national level, Intra-Refinery and Inter-Refinery optimization is the second step in optimizing the operation of the whole refining chain as a single system. Most refinery-wide optimization methods do not cover multiple objectives such as minimizing environmental impact, avoiding catastrophic failures, or enhancing product spec upgrade effects. This work starts by carrying out a refinery-wide, single objective optimization, and then moves to multi objective-single refinery optimization. The last step is multi objective-multi refinery optimization, the objectives of which are analysis of the effects of economic, environmental, product spec, strategic, and catastrophic failure. Simulation runs were carried out using both MATLAB and ASPEN PIMS utilizing nonlinear techniques to solve the optimization problem. The results addressed the need to debottleneck some refineries or transportation media in order to meet the demand for essential products under partial or total failure scenarios. They also addressed how importing some high spec products can help recover some of the losses and what is needed in order to accomplish this. In addition, the results showed nonlinear relations among local and global objectives for some refineries. The results demonstrate that refineries can have a local multi objective optimum that does not follow the same trends as either global or local single objective optimums. Catastrophic failure effects on refinery operations and on local objectives are more significant than environmental objective effects, and changes in the capacity or the local objectives follow a discrete behavioral pattern, in contrast to environmental objective cases in which the effects are smoother. In addition, crude processing capacity is the main factor affecting the objectives, and results demonstrate the benefit of having more than one crude unit, which gives higher flexibility in running the refinery at low feed rates. Results demonstrate the importance of examining the effects of loss of internal processing flexibility, which may not be clear in either local or global objective functions and can have an effect on products supplies. For all objectives, one refinery price structure creates a conflict with global objectives due to demand constraints imposed on the refinery proper without crediting the refinery's local objective function for these imposed constraints.
Keywords: chemical engineering; environmental engineering; environmental science; energy; petroleum engineering